ETHNOMATEMATIKA PADA PERMAINAN GASING MELAYU SAMBAS - Sumi; Septianawati, Desty (Uninus Journal of Mathematics Education and Science (UJMES), 2026)
The aim of this research is to find out mathematical concepts in the form of set concepts and probability concepts that exist in the spinning top game of the people of Sambas Regency. This type of method uses a qualitative descriptive method with an ethnographic approach. This approach aims to collect data in the form of words and pictures about the top game, by watching children play tops. The subjects of this research were 4 people consisting of 2 adults and 2 children from Sambas Regency, Tebas District, Pangkalan Kongsi Village Rt004/Rw002. In this study, researchers observed whether students knew that culture and mathematics were interconnected and is usually called ethnomathematics and whether they were aware of the mathematical component in the top game. Therefore, to find out the relationship between culture and mathematics in the top game, the researcher gave a few examples in the form of descriptions of alternative mathematics learning in the top game. In conclusion, after they play the spinning top game, students can understand the mathematical concepts contained in this traditional game.